1996
DOI: 10.1002/(sici)1097-0185(199608)245:4<699::aid-ar10>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of vinculin in the heart of the early developing rat embryo

Abstract: Background The interaction of cells and extracellular matrix (ECM) components is important in the morphogenesis of the developing heart and is thought to be mediated in part by adhesion plaques associated with vinculin, paxillin, talin, integrin, and other proteins. We investigated the patterns of expression of vinculin in the early embryonic rat heart to evaluate the role of vinculin in cardiac morphogenesis. Methods Vinculin expression was studied immunohistochemically in developing Sprague‐Dawley embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the light of the detected molecular link of TF's cytoplasmic domain to ABP‐280 in actin filament‐rich membrane areas of epithelial cells12, 13, the predominant localization of TF in the transverse parts of myocardial IDs indicates that TF may be associated with the actin filament system in the fasciae adherentes of contractile fibres. Double immunofluorescence demonstrated that TF was detectable in IDs together with a number of proteins, such as vinculin, known to be present in the dense material of fasciae adherentes22, 34, 37, 38. An interaction between TF and other specialized junctions, such as desmosomes, and unspecialized unit membrane portions of the IDs cannot, however, be excluded.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the light of the detected molecular link of TF's cytoplasmic domain to ABP‐280 in actin filament‐rich membrane areas of epithelial cells12, 13, the predominant localization of TF in the transverse parts of myocardial IDs indicates that TF may be associated with the actin filament system in the fasciae adherentes of contractile fibres. Double immunofluorescence demonstrated that TF was detectable in IDs together with a number of proteins, such as vinculin, known to be present in the dense material of fasciae adherentes22, 34, 37, 38. An interaction between TF and other specialized junctions, such as desmosomes, and unspecialized unit membrane portions of the IDs cannot, however, be excluded.…”
Section: Discussionmentioning
confidence: 95%
“…TF mRNA and TF protein are expressed by myocardial cells in both human and murine heart anlage. Interactions between the extracellular matrix, the cell surface, and the cytoskeleton mediated by transmembrane proteins appear to be critical in the cell sorting and organization that is fundamental to cardiac development19–22. During cardiogenesis, and in the mature heart under certain physiological conditions such as physical stress, a spatial and temporal expression pattern and variable structural organization of various structural proteins in cardiomyocytes are known23–25.…”
Section: Introductionmentioning
confidence: 99%